Sustainability impact assessments of free trade agreements A critical review - Moïsé, Evdokia (OECD Trade Policy Papers, 2021)
Trade negotiations are frequently accompanied by sustainability impact assessment (SIA) to evaluate the potential economic, environmental, social and human rights effects of a possible agreement. SIAs can help promote environmental protection, and support the better integration of women, vulnerable populations, and small businesses into the global economy, as well as address growing concerns from civil society. They provide a critical opportunity for dialogue among stakeholders and trade policy makers, and thereby help to rebuild confidence in the trading system. However, SIA approaches ‒ including economic modelling, qualitative causal chain analysis and stakeholder consultations ‒ each have their strengths, challenges and limitations. Those need to be understood by policy makers if reliable and policy relevant conclusions are to be provided. This paper offers a perspective on the challenges and opportunities of various approaches and discusses best practices for assessing the sustainability impact of trade and trade agreements